Sociality, temporality and locality in a contemporary Inuit community - Stuckenberger, A. (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractMauss (1906) suggested that, as a principle of Inuit society, the seasonal societal dichotomy takes shape in movements of population concentration and dispersal into small family groups following the annual migration of game. He argued that these movements and the various social modes thus created inseparably connect temporal, spatial, social, moral, legal, and spiritual dimensions in the construction of Inuit nomadic society. In the mid 20th century, the mass and density of Inuit settlement population changed drastically. Inuit groups moved to permanent settlements that were developed and structurally based on Western models of sedentary community life. Under these changed social and physical conditions, does movement and seasonal variations in group composition, and in ways of life, continue to be a central component of Inuit society? Ethnographic evidence from Qikiqtarjuaq (Nunavut) suggests that Inuit integrate modern ways of life into a nomadic lifestyle thus creating, in analogy to Mauss’s model, a continuation of variation in lifestyles and values depending on contexts. This article aims to substantiate and elaborate on this claim of continuity. It makes use of Mauss’s model as a heuristic lens for studying social change in respect to the association of practices and perceptions of seasonal movement in present day Inuit society; thus asking the question: are seasonally varying social modes and associated values part of today’s Inuit community constitution?